2020
DOI: 10.5114/aoms.2020.92434
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and psoriasis: a meta-analysis of observational studies with non-psoriasis control groups

Abstract: Introduction: Psoriasis is a highly prevalent condition that affects the quality of life of affected individuals. Several studies have indicated an association between psoriasis and metabolic syndrome (MS). However, the results were inconsistent. The objective of this study was to evaluate the relationship between psoriasis and MS. Material and methods: Electronic databases (PubMed, EBSCO, Elsevier, Springer, Wiley, and Cochrane) were searched systematically for published studies up to November 2, 2018. Odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
1
8
0
4
Order By: Relevance
“…Despite the heterogenicity of the studies in the case of psoriasis, our results indicated a strong correlation with MetS. In line with our study, a systematic review with a total of 137,053 participants illustrated that psoriasis was correlated with MetS (combined OR: 2.02, 95% CI: 1.67−2.43) 61 . Moreover, another systematic meta‐analysis with the Latin American population claimed that psoriasis and MetS are significantly correlated (pooled OR: 1.66, 95% CI: 1.27−21.42) 62 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the heterogenicity of the studies in the case of psoriasis, our results indicated a strong correlation with MetS. In line with our study, a systematic review with a total of 137,053 participants illustrated that psoriasis was correlated with MetS (combined OR: 2.02, 95% CI: 1.67−2.43) 61 . Moreover, another systematic meta‐analysis with the Latin American population claimed that psoriasis and MetS are significantly correlated (pooled OR: 1.66, 95% CI: 1.27−21.42) 62 .…”
Section: Discussionsupporting
confidence: 88%
“…In line with our study, a systematic review with a total of 137,053 participants illustrated that psoriasis was correlated with MetS (combined OR: 2.02, 95% CI: 1.67−2.43). 61 Moreover, another systematic meta‐analysis with the Latin American population claimed that psoriasis and MetS are significantly correlated (pooled OR: 1.66, 95% CI: 1.27−21.42). 62 Further, a higher risk of MetS was detected in patients with chronic and severe forms of psoriasis (pooled OR: 6.65, 95% CI: 3.32−13.31).…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis had an adverse effect on metabolic disease in both adults and children. There were statistically significant associations found between psoriasis and incidence of obesity ( 42 ), diabetes ( 43 ), and metabolic syndrome ( 44 ) in adults. Sincerely, psoriasis also increased the risk of developing overweight ( 30 ), hyperlipidemia ( 30 ), metabolic syndrome ( 30 ), obesity ( 29 ), diabetes, ( 29 ) and dyslipidemia ( 29 ) in children ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the metabolism of carbohydrates and lipids is deeply altered [99,100], but also that of proteins/amino acids [101]. The effects of MS seem to be most crippling on the liver [102][103][104], heart, and vessels [105][106][107][108], as well as the endocrine (such as gonads and adrenals) [109,110] and immune [111,112] systems, but practically every organ and tissue is affected: the brain [113,114], kidneys [108,115], skeletal muscle [116,117], connective tissue [117,118] (adipose [119,120]), lung and respiration [121,122], bone and cartilage [123,124], skin [125,126], including our different microbiota niches [127][128][129]. The degree of intensity of affectation of organs/systems may vary, but the extension of the consequences (i.e., overall endocrine and defense milieu, redox state [130,131], substrate partition [132,133], and handling) affect the whole body.…”
Section: Pathologic Traits Of the Ms Cluster 21 Components Of The Msmentioning
confidence: 99%